PENERAPAN KEBIJAKAN REFOCUSING DALAM MENGHADAPI PANDEMI COVID-19 TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA MISLAK KABUPATEN BANGKA BARAT DITINJAU DARI UNDANG-UNDANG NOMOR 2 TAHUN 2020 TENTANG PENETAPAN PERPPU NOMOR 1 TAHUN 2020 - Virna Dewi (Fakultas Hukum Universitas IBA Palembang, 2022)
The current government of the Unitary State of the Republic of Indonesia certainly has policies, especially in the context of implementation. Public policy is an action taken by the government, and public policy is a government decision that has a specific purpose. The Covid-19 pandemic has had a tremendous impact on the national economy and the socio-economic conditions of the community. Village development is an effort to improve the quality of life of the community, therefore, village development planning must be carried out properly and effectively so as to provide benefits and progress for the local community. How is the refocusing policy implemented in Mislak Village, Jebus District, West Bangka Regency based on Law Number 2 of 2020? What is the impact of the refocusing policy on infrastructure development in Mislak Village, Jebus District, West Bangka Regency? In the event that the Village Government does not distribute the Village BLT for nine months in the 2020 fiscal year, it will be subject to sanctions. The Mislak Village Government, Jebus District, West Bnagka Regency prioritizes the development of human resources or non-physical development, especially in the field of education.